Analysis of extreme climate indicators and local perception in two communities of the Lacandon Rainforest - Álvarez-Vázquez, José Luis; Aguilar-Sánchez, Genaro; Granados-Ramírez, Rebeca; Duch-Gary, Jorge; Juárez-Méndez, Juan; Tamara-Pedron, Isabel (Revista Mexicana de Ciencias Agrícolas, 2023)
AbstractIn the present study, the climate change indices of the Lacantún climate station, Mexico, and their influence on the agricultural field (milpa system) in two communities of the Lacandon Rainforest region were analyzed. The detection of changes and identification of temperature and precipitation trends in the study area was carried out by calculating the indices proposed by the expert team on climate change detection and indices through the RClimdex program. In addition, through interviews with the local population, the perception of climate changes and their impact on agriculture was known. The results indicate that, from 1980 to 2016, there was an increase of 1.5 °C in the maximum temperature, an increase of 0.5 °C in the minimum temperature, precipitation decreased by 500 mm, dry days increased, and wet days did not vary. According to the perception of the population, there is a delay and a decrease in rains, delaying sowings for up to 20-30 days, the dog days have extended 10 or 15 more days, there is a greater presence of pests and diseases (fall armyworm and bean rust); these changes have caused yield reductions of 20-25% in corn and 20-30% in beans.
Keywords: climate change; precipitation; RClimdex; temperature